Targeting protein homeostasis with small molecules as a strategy for the development of pan-coronavirus antiviral therapies - Yu-Qian Mao; Shahrzad Jahanshahi; Ramy Malty; David A. J. Van Ommen; Yimei Wan; Trevor M. Morey; Stephanie H. W. Chuang; Veronika Pavlova; Choudhary Ahmed; Subha Dahal; Funing Lin; Maria Mangos; et al. (Communications Biology)
Abstract The COVID-19 pandemic has created a global health crisis, with challenges arising from the ongoing evolution of the SARS-CoV-2 virus, the emergence of new strains, and the long-term effects of COVID-19. Aiming to overcome the development of viral resistance, our study here focused on developing broad-spectrum pan-coronavirus antiviral therapies by targeting host protein quality control mechanisms essential for viral replication. Screening an in-house compound library led to the discovery of three candidate compounds targeting cellular proteostasis. The three compounds are (1) the nucleotide analog cordycepin, (2) a benzothiozole analog, and (3) an acyldepsipeptide analog initially developed as part of a campaign to target the mitochondrial ClpP protease. These compounds demonstrated dose-dependent efficacy against multiple coronaviruses, including SARS-CoV-2, effectively inhibiting viral replication in vitro as well as in lung organoids. Notably, the compounds also showed efficacy against SARS-CoV-2 delta and omicron strains. As part of this work, we developed a BSL2-level cell-integrated SARS-CoV-2 replicon, which could serve as a valuable tool for high-throughput screening and studying intracellular viral replication. Our study should aid in the advancement of antiviral drug development efforts.